ANALISIS KERJASAMA AKTOR-AKTOR NON PEMERINTAH DALAM PENINGKATAN SUMBER DAYA MANUSIA SEBAGAI INDIKATOR KEBERHASILAN PEMBANGUNAN PENDIDIKAN - Talakua, Jeane F.D.; Wiloso, Pamerdi Giri; Therik, Wilson M.A. (Universitas Kristen Satya Wacana, 2016)
The article describes the cooperation of non-governmental actors conducted by Christian High School 1 Salatiga and the Institute of Chinese Language Course